2004
DOI: 10.1002/ange.200460327
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Tricolorin A: Molecular Rationale for the Biological Properties of Resin Glycosides Found in Some Mexican Herbal Remedies

Abstract: Ein Wasserkanal wurde in der ersten kristallographisch bestimmten Struktur eines natürlichen Harzglycosids nachgewiesen (siehe Bild). Die amphipatischen Charakteristika von Tricolorin A korrelieren mit einer signifikanten Säuger‐ und Pflanzentoxizität. Die Architektur von Tricolorin A im Festkörper lässt vermuten, dass die Cytotoxizität dieser Verbindungsklasse das Ergebnis ihrer Porenbildungsfähigkeit ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Intrinsic glycan flexibility limited the use of such strategies. However, recent works showed that short oligosaccharides can adopt stable structures in solution, influencing their binding. ,, Moreover, especially in plants, many examples of macrocyclic tethered oligosaccharides (e.g., tricolorin and calonyctin A) with interesting biological activities were identified. , As a consequence, artificial constrained oligosaccharides gained popularity (Figure ). Preorganized glycans pay a lower flexibility-induced entropic cost upon binding, resulting in higher affinity constants.…”
Section: Toward Sugar Foldamersmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic glycan flexibility limited the use of such strategies. However, recent works showed that short oligosaccharides can adopt stable structures in solution, influencing their binding. ,, Moreover, especially in plants, many examples of macrocyclic tethered oligosaccharides (e.g., tricolorin and calonyctin A) with interesting biological activities were identified. , As a consequence, artificial constrained oligosaccharides gained popularity (Figure ). Preorganized glycans pay a lower flexibility-induced entropic cost upon binding, resulting in higher affinity constants.…”
Section: Toward Sugar Foldamersmentioning
confidence: 99%
“…[16][17][18][19]94,95 Moreover, especially in plants, many examples of macrocyclic tethered oligosaccharides (e.g., tricolorin and calonyctin A) with interesting biological activities were identified. 96,97 As a consequence, artificial constrained oligosaccharides gained popularity (Figure 10). Preorganized glycans pay a lower flexibility-induced entropic cost upon binding, resulting in higher affinity constants.…”
Section: Conformational Locksmentioning
confidence: 99%
“…[8][9][10] Resin glycosides exhibit a broad spectrum of biological activities, ranging from laxative, purgative, haemolytic, antibacterial, antifungal or plant growth inhibitory properties to significant cytotoxicity. [1][2][3][4] However, the understanding for their mode of action is largely missing, [11] as are systematic studies into structure-activity relationships. The available information, however, suggests that these compounds offer ample opportunity for optimization of their bioactivity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…22 This supports the hypothesis proposed by Pereda− Miranda and colleagues that some biological potential of the resin glycosides may rely on their pore-forming properties to provoke an imbalance in cellular homeostasis. 6,23 ■ EXPERIMENTAL SECTION General Experimental Procedures. Optical rotations were obtained on a JASCO P-1020 polarimeter.…”
Section: ■ Results and Discussionmentioning
confidence: 99%